South African market access challenges in the European Union : a case of regulatory compliance and non-tariff measures - Kalaba, Mmatlou W. (University of Pretoria, 2023)
Dissertation (MSc (Agric) Agricultural Economics and Agribusiness Management)--University of Pretoria, 2023.